2009
DOI: 10.1073/pnas.0911987106
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifier screen identifies HDAC inhibitors as suppressors of PKD models

Abstract: Polycystic kidney disease (PKD) is a common human genetic disease with severe medical consequences. Although it is appreciated that the cilium plays a central role in PKD, the underlying mechanism for PKD remains poorly understood and no effective treatment is available. In zebrafish, kidney cyst formation is closely associated with laterality defects and body curvature. To discover potential drug candidates and dissect signaling pathways that interact with ciliary signals, we performed a chemical modifier scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 41 publications
5
157
0
3
Order By: Relevance
“…Besides interfering with angiogenic blood vessels formation, the compounds from valproylglycine hydrazide series also induced severe cardiac edema (Figure 1 black arrow in D). The cardiac edema has also been shown in previous studies which are HDAC mutant (Pillai et al, 2004;Yamaguchi et al, 2005) or embryos were treated with VPA or any other HDAC inhibitor (Farooq et al, 2008;Cao et al, 2009;Johnson et al, 2013). We have not analyzed the HDAC enzymatic activity with these compounds but most likely that the cardiac edema which is result of newly synthesized VPA derivatives could be due to their HDAC inhibition activity.…”
Section: Muhammad Farooq Et Almentioning
confidence: 77%
“…Besides interfering with angiogenic blood vessels formation, the compounds from valproylglycine hydrazide series also induced severe cardiac edema (Figure 1 black arrow in D). The cardiac edema has also been shown in previous studies which are HDAC mutant (Pillai et al, 2004;Yamaguchi et al, 2005) or embryos were treated with VPA or any other HDAC inhibitor (Farooq et al, 2008;Cao et al, 2009;Johnson et al, 2013). We have not analyzed the HDAC enzymatic activity with these compounds but most likely that the cardiac edema which is result of newly synthesized VPA derivatives could be due to their HDAC inhibition activity.…”
Section: Muhammad Farooq Et Almentioning
confidence: 77%
“…In this type of experiment, hundreds or even thousands of small batches of embryos are each exposed to a different chemical compound, and analyzed for developmental or behavioral changes. Such an approach has been applied either to wild-type embryos or to carriers of genetic defects (Cao et al, 2009;North et al, 2007North et al, , 2009Peterson et al, 2004). In the latter case, compounds that rescue a mutant phenotype can be screened for.…”
Section: Chemical Screensmentioning
confidence: 99%
“…It has been demonstrated that p53 functions as a negative regulator of Pkd1 gene transcription by binding to the Pkd1 gene promoter in vivo. Importantly, trichostatin A (TSA), a general inhibitor of class I and II HDACs, has been shown to abolish the p53-mediated repression of Pkd1 gene expression in Pkd1 mutant mice (67,68). This indicates that p53 negatively controls Pkd1 gene expression in cooperation with HDACs and may contribute to deregulated Pkd1 expression and cyst formation (67).…”
Section: The Functional Role Of Hdacs In Pkdmentioning
confidence: 99%
“…The results of recent studies have demonstrated that the acetylation of histone lysine residues might be correlated with PKD and CKD pathogenesis (27,28,(67)(68)(69). The PKD1 gene is the most critical factor in ADPKD pathogenesis (1).…”
Section: The Functional Role Of Hdacs In Pkdmentioning
confidence: 99%
See 1 more Smart Citation